EFEKTIVITAS PELAYANAN PEMBUATAN KTP-EL MELALUI APLIKASI SISTEM INFORMASI ADMINISTRASI KEPENDUDUKAN (SIAK) DI DINAS KEPENDUDUKAN DAN PENCATATAN SIPIL KABUPATEN DELI SERDANG - Ismaysiktah, Lika; Sihombing, Tunggul; Yanty S. Siahaan, Asima (ITB AAS Indonesia Surakarta, 2025)
This study analyzes the effectiveness of e-KTP services through the Population Administration Information System (SIAK) application at the Department of Population and Civil Registration of Deli Serdang Regency. This research focuses on the importance of digitalizing public services to enhance efficiency, transparency, and accessibility for the community. A qualitative descriptive approach was used in this study, with data collected through interviews, observations, and documentation. The findings indicate that the implementation of SIAK has accelerated the issuance process of e-KTP, with an estimated printing time of approximately five minutes after submission. However, several challenges were encountered in implementing this system, including the public’s limited understanding of technology, infrastructure constraints, and technical issues in system operations. Additionally, resistance to change and limitations in human resources have also hindered service effectiveness. Overall, the application of SIAK in the Deli Serdang Regency has significantly improved administrative services for population registration. However, further optimization is needed regarding human resource training, infrastructure enhancement, and public outreach to ensure the system operates more effectively and sustainably.